A Study on Diagnostic Evaluation of Two Different Rapid DNA Polymerase Chain Reaction Techniques Namely Gene Xpert Mycobacterium Tuberculosis/Rifampin (MTB/RIF) and Mycoreal Polymerase Chain Reaction in the Diagnosis of Endometrial Tuberculosis Considering Culture as Gold Standard - M Ashwini; N Ashwini; N Arunkumar; Devika Gunasheela (Journal of Human Reproductive Sciences, 2020)
Context: The study involves the evaluation of two polymerase chain reaction (PCR) techniques one of which has been endorsed by the WHO for their diagnostic capabilities. Aims: The aim of this study is to evaluate the diagnostic accuracy of GeneXpert mycobacterium tuberculosis/Rifampin (MTB/RIF) and mycoreal PCR techniques in the diagnosis of endometrial tuberculosis (TB) considering culture as the gold standard. Settings and Design: A retrospective study conducted at Gunasheela surgical and maternity hospital. Patients who attended the outpatient department between January 2013 and August 2016, satisfying the eligibility criteria, were included in the study. Methodology: Women included in the study underwent endometrial pipelle sampling premenstrually after ruling out pregnancy in that cycle. Endometrial samples were tested for TB by Mycoreal PCR, Gene Xpert and BACTEC culture. Statistical Analysis Used: Statistical analysis was done using the R software version 3.6.1. Sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and accuracy of test were calculated. Results: A total of 3229 samples were analyzed, of which 1754 were evaluated by Mycoreal TB PCR and 1475 were evaluated by Gene Xpert MTB/RIF assay. The sensitivity of mycoreal TB PCR technique was 34.78%, specificity was 99.08%, PPV was 33.33%, NPV was 99.13%, and accuracy was 98.23%. The sensitivity of GeneXpert MTB/RIF technique was 6.90%, specificity was 99.79%, PPV was 40.00%, NPV was 98.16%, and accuracy was 97.97%. Conclusions: MYCOREAL seemed to be more sensitive than Gene Xpert (MTB/RIF) considering culture as the gold standard in the diagnosis of endometrial TB.